Keuangan Dan Pembiayaan Bagi Generasi Milenial Dalam Perspektif Ekonomi Syariah - Neli Amellia; Annisha Tri Rahayu; Muhammad Firman Maulana; Ali Hasfan Soaduon Hasibuan; Al Hafiz; Naila Rahmawati; Sriwati (Journal of Economics and Business, 2024)
ABSTRACT Many consider the millennial generation, or the generation currently in their 20s and 30s, to be the worst at managing finance and financing. As for the purpose in writing this journal to find out the financial and financing activities of the millennial generation, it uses a qualitative descriptive research method with a literature approach. The results of the study describe that one of the strategies that can be applied in finance and financing is to prepare a careful budget, prioritize in spending, investment is certainly based on the principles of transparency, justice, and social responsibility. In financing there are several instruments such as sharia bonds or social investment products and increasing financial literacy. Abstrak Banyak yang menilai generasi milenial, atau generasi yang saat ini berusia 20-an dan 30-an, adalah generasi yang paling buruk dalam mengelola keuangan dan pembiayaan. Adapun tujuan dalam penulisan jurnal ini untuk mengetahui aktivitas keuangan dan pembiayaan generasi milenial, maka menggunakan metode penelitian deskriptif kualitatif dengan pendekatan kepustakaan. Hasil penelitian mendeskripsikan bahwa salah satu strategi yang dapat diterapkan dalam keuangan dan pembiayan yaitu menyusun anggaran yang teliti, prioritas dalam pengeluaran, investasi tentu didasari dengan prinsip transparansi, keadilan, dan tanggung jawab sosial. Dalam pembiayaan ada beberapa instrumen  seperti obligasi syariah atau produk investasi social serta meningkatkan literasi keuangan.